First Approval of Pacritinib as a Selective Janus Associated Kinase-2 Inhibitor for the Treatment of Patients with Myelofibrosis - De, Surya K. (Anti-Cancer Agents in Medicinal Chemistry, 2023)
Myelofibrosis is one kind of bone marrow blood cancer that gives mainly bone marrow scarring. JAK families include JAK1, JAK2, JAK3, and tyrosine kinase 2 (TYK2) and they control hematopoiesis and immune cell function. JAK-STAT pathways have the critical roles in the pathogenesis of a variety of autoimmune and inflammatory diseases such as myelofibrosis. The 8 JAK inhibitors are approved by the US FDA for the treatment of various diseases. Abrocitinib, baricitinib, oclacitinib, ruxolitinib, tofacitinib, upadacitinib, fedratinib, and pactrinib with their IC50 values against JAK1, JAK2, JAK3, and TYK2 are included. All approved JAK inhibitors with structural similarities and dissimilarities are summarized. The development story of pacritinib and new design route to overcome intellectual property-related issues by connecting the A ring and C ring to form the macrocyclic compounds like 16 without compromising the binding modes in the hinge region are discussed. By using the powerful ring-closing metathesis (RCM), they designed and synthesized and delivered FDA approved pacritinib. In this short perspective, the chemical structure, physicochemical properties, mechanism of action, drug-interactions, adverse events, and pharmacokinetic profile of pacritinib are summarized. Detailed step by step synthesis of pacritinib is provided. Pacritinib is an orally bioavailable and isoform selective JAK-2 inhibitor for the treatment of patients with myelofibrosis. Detailed metabolism pathway with proper explanation is discussed.
Keywords: Janus kinase